1981
DOI: 10.1007/bf02318918
|View full text |Cite
|
Sign up to set email alerts
|

Callus induction and plant regeneration from immature embryos of rye and triticale

Abstract: Abstract. Callus cultures were established from the scutellum, scuteUar node and radicle region of immature embryos of rye and octoploid triticale on modified MurashigeSkoog basal medium supplemented with various growth regulators. 2, 4-D, 2, 4, 5-T and 2, 4, 5-CI3POP were found suitable for initiation and maintenance of callus cultures. Cytokinins had no or inhibitory effect on callus induction and growth. On basal medium containing 5 mg/1 of 2,4,5-C13 POP, 16% of triticale and 17% of rye primary cultures exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Other auxins p-CPA, 2, 4, 5-C1 3 POP have also been found useful for callus production (Eapen & Rao, 1982, Krumbiegel-Schroern et al ., 1984 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other auxins p-CPA, 2, 4, 5-C1 3 POP have also been found useful for callus production (Eapen & Rao, 1982, Krumbiegel-Schroern et al ., 1984 .…”
Section: Introductionmentioning
confidence: 99%
“…Histological examination of proliferating tissue revealed that callus was initiated from the scutellar node and the region of the radical and plumule 5 9 (Eapen & Rao, 1982) . In the case of isolated scutellum parenchyma cells, divisions occurred on different parts of explants (Rybczynski, 1979) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations